A Rare Case of Mixed Neuroendocrine Tumor and Adenocarcinoma of the Pancreas - Sofia Xenaki; Konstantinos Lasithiotakis; Alexandros Andreou; Sofia Aggelaki; Maria Tzardi; Anna Daskalaki; George Chalkiadakis; Emmanuel Chrysos (Case Reports in Surgery)
Introduction. Neuroendocrine carcinoma (NEC) of pancreas is a rare tumor with aggressive progression and poor prognosis. Its coexistence with adenocarcinoma poses significant clinical problems and has not been addressed in the literature. Methods. We describe a case of a 51-year-old male who underwent pancreatoduodenectomy due to pancreatic head tumor 1.5×1×1.4 cm. Histological examination of the specimen revealed a mixed neoplasm: (1) a well differentiated adenocarcinoma, neoplastic blasts of which are extended focally to the submucosa without invading the muscular layer, and (2) a low differentiated NEC consisting of solid clusters and pagetoid formations. All 18 lymph nodes of the specimen were free of neoplastic disease and the surgical margins of the specimen were tumor-free. No adjuvant treatment was administered and two months after the operation the patient developed liver metastasis. FNA cytology of the hepatic lesions revealed low grade carcinoma with neuroendocrine characteristics. Five lines of chemotherapy were administered: VP + CDDP, paclitaxel + ifosfamide + Mesna + CDDP, Folfox + Avastin, Folfiri + Avastin, and CAV. During his treatment he revealed PD and succumbed to his disease 13 months after the operation. Conclusion. Coexistence of NEC with adenocarcinoma of the pancreas is a very rare entity presenting significant challenges regarding its adjuvant treatment and the treatment of distant relapse.